CK2 inhibition with silmitasertib promotes methuosis-like cell death associated to catastrophic massive vacuolization of colorectal cancer cells - Silva Pavez, Eduardo (2019)
Protein kinase CK2 is a highly conserved and constitutively active Ser/Thr-kinase that phosphorylates a large number of substrates, resulting in increased cell proliferation and survival. A known target of CK2 is Akt, a player in the PI3K/Akt/mTORC1 signaling pathway, which is aberrantly activated in 32% of colorectal cancer (CRC) patients. On the other hand, mTORC1 plays an important role in the regulation of protein synthesis, cell growth, and autophagy. Some studies suggest that CK2 regulates mTORC1 in several cancers. The most recently developed CK2 inhibitor, silmitasertib (formerly CX-4945), has been tested in phase I/II trials for cholangiocarcinoma and multiple myeloma. This drug has been shown to induce autophagy and enhance apoptosis in pancreatic cancer cells and to promote apoptosis in non-small cell lung cancer cells. Nevertheless, it has not been tested in studies for CRC patients. We show in this work that inhibition of CK2 with silmitasertib decreases in vitro tumorigenesis of CRC cells in response to G2/M arrest, which correlates with mTORC1 inhibition and formation of large cytoplasmic vacuoles. Notably, molecular markers indicate that these vacuoles derive from massive macropinocytosis. Altogether, these findings suggest that an aberrantly elevated expression/activity of CK2 may play a key role in CRC, promoting cell viability and proliferation in untreated cells, however, its inhibition with silmitasertib promotes methuosis-like cell death associated to massive catastrophic vacuolization, accounting for decreased tumorigenicity at later times. These characteristics of silmitasertib support a potential therapeutic use in CRC patients and probably other CK2-dependent cancers.